330 SAFETY AND EFFICACY OF RETREATING FOLLICULAR NON-HODGKIN'S LYMPHOMA WITH 90Y IBRITUMOMAB TIUXETAN (ZEVALIN). Issue 1 (1st January 2007) - Shah, J.; Mueh, J.; Lister, J.; Jasthy, S.; Gregory, M.; Mckay, C.; Krumdieck, R.; Forero, A.
Abstract : Background: There are no data regarding safety and efficacy of treating follicular non-Hodgkin's lymphoma (NHL) patients with a second course of Zevalin. Methods: Patients with follicular NHL who received two courses of Zevalin therapy were identified nationally, and data were retrospectively collected. Results: Ten patients (mean age 62.5 years, 48-91) were identified. Prior to the first Zevalin, all patients received chemotherapy (mean 2.4 courses, 1-5), 3 of 10 auto-PBSCT, and 4 of 10 external beam radiotherapy (ebRT). After the initial course of treatment, the mean time to nadir for the anemia was 7.9 weeks (4-13), neutropenia was 6.7 weeks (4-10), and thrombocytopenia was 5.2 weeks (4-8). One patient required growth factor support and transfusions; two had an incomplete recovery of platelet count at 23 and 30 weeks (76, 000 and 126, 000/μL). Hematologic toxicity and grades are in the table below. Prior to the second course of Zevalin two patients received ebRT, one received 131 I tositumomab, and three received chemotherapy (1-5 regimens). The median time to the second Zevalin course was 613 days (183-1, 300). After the second course of Zevalin, the mean time to nadir for the anemia was 8.2 wks (2-25); neutropenia was 6.7 weeks (4-10); and thrombocytopenia was 5.5 weeks (4-7). Four of 10 patients required growth factor support, 2 required transfusions, 3 had incomplete recovery of platelet count and early progression, and 2 had a maximum recovery of their platelet count at 29 and 40 weeks (143, 000 and 144, 000/μL). There were no infectious or bleeding complications with either course of Zevalin. No secondary myelodysplastic syndrome or acute leukemia was reported. Conclusions: Retreating patients with follicular NHL with a second course of Zevalin is tolerable, with substantial evidence of clinical efficacy.